(3GdESWSbGJ Ydi QCi HbQGWs - (3LGdjfhSs ((3eMeO Hf YHO GdSdGe s)
(3ChdgG (B:s
(3Efg deG cGf GdCSWbS Cbd LRAkG eeG ghdg CSWbS , hcGf GdLRA GdPi gh Cbd GdCLRGA ajeG jXgQ ddMS s
(3BNQgG (B:s
(3aHTOI GdLPH jJHYg hGMO ef SGFQ GdCNdGW , hgh GdPi jJdh ai WHjYI Pdc GdNdW jLJPH bSQkG Je cJGH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3GdfSNI HgG MhGTs
(3YdjgG ebGHdI Hbde eMeO Hf YHO GdSdGe SfI (B692(3g`s
(3hGfXQ agQS GdWH (B11 (3GdESWbSGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs